Sensory-Motor Amnesia and Somatic Solutions - Jeong Myung Gim (Asian Society of Kinesiology, 2018)
PURPOSE The purpose of this study was to identify the neurophysiological mechanisms of Sensory-Motor Amnesia (SMA) and to understand the clinical basis of Hanna's somatic education as a somatic solution. METHODS This study mainly focuses on the related literature studies. In order to understand the experiential properties of SMA and to enhance the credibility of the reference to Hanna's solution, the researcher visited the Novato institute developing Hanna Somatic Education 5 times and collected the data. RESULTS 1) Hanna's discovery of SMA was influenced by Hans Selye's general adaptation syndrome and 'stress' concept in that human physiological functions are not separated from psychological phenomena. At the same time after practical training under Feldenkrais' guide and observing clients from the first-person perspective, he realized the neurophysiological clue in his own practices. 2) SMA is a phenomenon of muscle contraction that occurs when the chronic stress reaction disturbs the autonomic nervous system. When the stress condition persists, it becomes an obstacle of the sensory-motor function in the unconscious area and paralyzes the inherent proprioceptive senses. It not only limits the range of intentional human movements but also acts as a cause of the structural distortion of the body. 3) Based on Alexander's Means-Whereby principle and Feldenkrais' Kinetic Mirroring, he developed a more effective technique, Pandiculation Response, to improve the clinical effectiveness to SMA problem. CONCLUSIONS Somatic Education is not a process from the third-person observation as the existing medical system but a process of integrating the third-person information centered on the first-person viewpoint, so the empirical basis should be established in a new integrated clinical system dealing with human soma.